2018
DOI: 10.1007/s00066-018-1269-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of androgen deprivation and salvage radiation therapy for patients with prostate cancer and biochemical recurrence after prostatectomy

Abstract: ADT combined with SRT appears to improve OS in patients with a PSA level before SRT of ≥0.7 ng/mL. In patients without persistent PSA after prostatectomy and PSA levels of <0.7 ng/mL, ADT should not routinely be used, but may be considered in patients with additional risk factors such as Gleason Score ≥8 and negative surgical margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Although our present patient numbers in the subgroups are too small for unequivocal conclusions, the observation of poor outcome in post‐RP PSA‐persistent patients with delayed SRT alone is consistent with a recent systematic review that reported that ADT combined with SRT improved OS in patients with a pre‐SRT PSA level of ≥0.7 ng/mL . The prospective randomised GETUG‐AFU 22 phase‐II trial () addresses the effect of 6 months ADT concomitant with SRT vs SRT alone in 125 patients with a ‘persistent’ PSA level after RP of ≥0.2 and ≤2 ng/mL at randomisation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although our present patient numbers in the subgroups are too small for unequivocal conclusions, the observation of poor outcome in post‐RP PSA‐persistent patients with delayed SRT alone is consistent with a recent systematic review that reported that ADT combined with SRT improved OS in patients with a pre‐SRT PSA level of ≥0.7 ng/mL . The prospective randomised GETUG‐AFU 22 phase‐II trial () addresses the effect of 6 months ADT concomitant with SRT vs SRT alone in 125 patients with a ‘persistent’ PSA level after RP of ≥0.2 and ≤2 ng/mL at randomisation.…”
Section: Discussionsupporting
confidence: 85%
“…Although our present patient numbers in the subgroups are too small for unequivocal conclusions, the observation of poor outcome in post-RP PSA-persistent patients with delayed SRT alone is consistent with a recent systematic review that reported that ADT combined with SRT improved OS in patients with a pre-SRT PSA level of ≥0.7 ng/mL [21].…”
Section: Variablesupporting
confidence: 90%
“…For patients with high risk disease shorter delays of 2-4 months but with ADT are recommended as a safe and pragmatic approach. Data also appears to support the use of ADT to delay radiotherapy in a post-prostatectomy salvage situation [33] Dose escalation studies in the definitive treatment of prostate cancer have failed to show overall survival benefit which in this scenario provides further comfort in using lower dose schedules [34]. When radiotherapy is required then, just as with breast, there is data to support both modest hypofractionation over 20 fractions (60Gy) or ultra hypo-fractionated regimens (42·7Gy in seven fractions, 3 days per week for 2·5 weeks) [35] or 36Gy in 6weeks [36].…”
Section: Prostate Cancermentioning
confidence: 87%
“…In total, there were 4 patients with a Clavien Grade II (2 × paralytic ileus, 2 × lymphorrhea) and 2 patients with a Clavien Grade IIIa (2 × pulmonary artery embolism) complication ( Table 2). ADT was recommended to all patients with SLNRT due to the evidence of PET-positive lymph nodes for 2 years [20,21]. Consequently, 59/67 (88%) patients were started on ADT before initiation of SLNRT, 42/67 patients (63%) discontinued after a median time of 7 (2-41) months due to patients' preferences.…”
Section: Management Of Pet-positive Lymph Nodes and Toxicitymentioning
confidence: 99%